EKSISTENSI KEHIDUPAN BURUH GENDONG PEREMPUAN DI PASAR BERINGHARJO YOGYAKARTA - Trina Melianingsih, Sheila Oksapariana a * (Dimensia: Jurnal Kajian Sosiologi, 2008)
The theme of this research is about the strategy of labor carriers (buruh gendong) to exist in facing the various life dynamics around the area of Beringharjo market, Yogyakarta. Researcher desire to know how the strategy or effort done by all labor in order to take care of themselves existence and also how the role of the social capital that playing in a part of its effort. Strategy can be formulated as effort to take care of themselves existence as labor carry on the back woman at Beringharjo market. Method used in this research is the descriptive qualitative method. In this research, there are six labors of women carriers (buruh gendong perempuan) that still active work around the area of Beringharjo market taken as the informant object. According to them, we know how their efforts and strategy done to take care of themselves existence in facing of the dynamics life at Beringharjo market. One of their strategies is join the labor group in the area of Beringharjo market. Sayuk Rukun Association directs under construction an institution which interest in charwoman activity. A lot of efforts developed, for example cooperation, saving and loan and religious activity which usually always continued with the activity of health service. In religious activity, it also gives some materials to add their knowledge. In this research found some factors related to the background of the existence of labor woman carriers (buruh gendong perempuan) and also efforts done to maintain themselves in facing of market economics.   Keyword: Existence, Labor, Woman Carrier